Epidemiology of deep cutaneous fungal infections in Korea (2006–2010). Issue 10 (24th June 2015) - Kim, Myoung Shin; Kim, Jae Kyung; Lee, Mi Woo; Moon, Kee‐Chan; Kim, Beom Joon; Son, Sang Wook; Ahn, Hyo Hyun; Oh, Sang Ho; Yu, Hee Joon; Lee, Dong Youn; Cho, Kwang Hyun; Cho, Baik Kee; et al.
Abstract Deep cutaneous fungal infections (DCFI) occur worldwide and their prevalence is influenced by personal factors of the affected patients and the geographic and cultural features. Surveillance studies of DCFI with respect to the various clinical backgrounds of affected patients can ultimately help to improve their outcome. Expanding on our previous study, we performed a retrospective analysis of patients with DCFI who were treated in a group of university teaching hospitals in Korea to determine the trends within a 5‐year period. A retrospective medical record review of patients with DCFI treated between 2006 and 2010 at 16 university teaching hospitals located throughout Korea was performed. Among the 51 cases of DCFI (median patient age, 47.0 years), opportunistic infections in immunocompromised hosts accounted for half. Patients in this group included 11 who were transplant recipients and 12 with malignancies. Overall, Candida (13/51) was the most common causative organism, followed by Sporothrix (12) and Aspergillus (6). Papuloplaques and nodular lesions were the typical presentation, with maculopatches and ulcers also occurring in considerable numbers. Ten patients had systemic involvement. Eight immunocompromised patients did not recover from the disease despite systemic antifungal treatment. Our results highlight the equal involvement of opportunistic and primary pathogens in DCFI, as determined in cases from a 5‐year period. Especially in immunocompromised hosts with non‐specific skin findings, clinical suspicion is important because failure to diagnose a DCFI causes significant morbidity and possibly even death.